Axes of relationship value between manufacturers and retailers. Issue 8 (12th April 2018) - Ruiz-Martinez, Alfonso; Gil-Saura, Irene; Frasquet, Marta
Abstract : Purpose: The purpose of this paper is to define the relationship strategy of manufacturers with their retail customers through the identification of axes for the creation of relationship value. Design/methodology/approach: A survey was carried out and 219 valid questionnaires were completed and returned by the purchasing managers of retail companies in the furniture sector. The model was estimated using the partial least squares approach. Findings: The results revealed three axes of value creation: the core axis, the information and communication technologies (ICTs) axis, and the access axis. These axes included the benefits and costs related to the product and the service provided, the ICTs of the manufacturing project, and the relationships with the sales personnel. Research limitations/implications: Due to the size of the sample, the authors were unable to analyse the potential unobserved heterogeneity of the sample. The authors would suggest that this aspect should be analysed in future research in order to attempt to segment clients. Practical implications: Seller support is the main element of value creation. The importance of the efforts made by management to strengthen the capacities of the field force may be highlighted. Originality/value: The main contribution of this study has been to increase the level of abstraction of the study of relationship value through the identification and modelling of its axes of creation for the under-researched retailers-suppliers relationship.